2020
DOI: 10.1111/and.13810
|View full text |Cite
|
Sign up to set email alerts
|

Low reduction of prostate volume is a significant predictor of prostate cancer at subsequent biopsy in patients with dutasteride: A retrospective study

Abstract: Appropriate decision of prostate biopsy in men with 5α‐reductase inhibitor (5AR inhibitor) is still unclear to avoid unnecessary biopsy. We retrospectively investigated patients with initial PSA 4.0 ng/ml or more and underwent subsequent prostate biopsy following dutasteride treatment. From September 2009 to August 2018, 399 cases of benign prostate hyperplasia (BPH) were treated with dutasteride in our department. Of the total, 36 cases with elevated pre‐treatment PSA (4.0 ng/ml or more) and underwent subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In addition to previous studies that reported that PSA density, prostate volume reduction rate, and MRI findings are important predictive factors for PCa detection, [11] we found that advanced age and abnormal MRI findings were clinically significant predictors of high grade PCa in BPH patients treated with dutasteride. The relationship between prostate cancer grade and age is controversial [15] ; however, in this study, age was found to be associated with high-grade prostate cancer in patients treated with dutasteride.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In addition to previous studies that reported that PSA density, prostate volume reduction rate, and MRI findings are important predictive factors for PCa detection, [11] we found that advanced age and abnormal MRI findings were clinically significant predictors of high grade PCa in BPH patients treated with dutasteride. The relationship between prostate cancer grade and age is controversial [15] ; however, in this study, age was found to be associated with high-grade prostate cancer in patients treated with dutasteride.…”
Section: Discussionsupporting
confidence: 68%
“…[11] However, our previous study was based on a small number of patients and did not evaluate comparative studies with patients not treated with dutasteride. [11] Also, the evaluation of biopsy core positivity rates was unknown in our previous study. [11] In this study, we have retrospectively compared the characteristics of prostate biopsies in BPH patients treated with dutasteride and in untreated patients, adjusted for PSA levels and age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations